Neurological manifestations of hereditary chromosomal diseases - L. B. Novikova; N. M. Faizullina; A. P. Akopyan; K. M. Ziultsle (Эпилепсия и пароксизмальные состояния, 2025)
The article describes three clinical cases of hereditary disorders associated with chromosomal mutations: deletions of chromosomes 14 and 18. These observations are of professional and scientific interest, since they relate to rare neurological pathology. The rarity of this anomaly, the presence of complications, the high cost of invasive diagnostics, the variability of the phenotype, including severe congenital malformations in children with microdeletions lead together to underdiagnosis of patients at the stage of prenatal diagnostics, which entails difficulties in selecting effective and safe therapy, a need for medical and psychosocial rehabilitation of children in society. In case of refractory epilepsy with developmental delay in infancy, typical to chromosomal microdeletions, genetic counseling and examination should be carried out to search for chromosomal pathology. Increasing the awareness of doctors about this disorder will contribute to its timely diagnostics and treatment.